Juridical Analysis Of Dispute Resolution In Online Arisan Agreements (Verdict Number 12/Pdt. G/2020/PN. Tpg) - Muhammad Rinaldi; Bachtiar Simatupang; Ramon Nofrial; Soerya Respationo; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
In today's modern era, all activities are beyond what is called technological progress, social media is now not only a medium to communicate but can also be a medium that can do investment activities. Man is called a creature homo economics (mahkluk ekonomi). This term is then now understood by most people with the meaning of a creature whose primary purpose in life is to seek profit. With the development of this era all investment activities can be done easily based on digital social media or online, one of the investment activities that can be made with online is online earnings, earnings in general is the activity of collecting money in groups formed by a member then determined how many times in a day or a week spend a month in such collection. after the money is collected then it is determined who will get the first number lottery to the end. With the development of this era online arisan activities are now also not only supported by adults but also by young people, for young people online Arisan becomes an investment choice because of the mechanisms that are quite easy, efficient, and encouraging, but not a little maintenance of this online aryan runs smoothly one of the cases of disadvantage against online arsan. The aim of this study is to find out the conclusion of a misconduct in an online arisan agreement between Umi Barokah (claimant I), Susanti (claimed II), Fransisca Irene Miranda Putty (claimer III), Erfira Meyer (claimsant IV) and the accused namely Anggie Nadia under Judgment No. 32./Pdt.G/2020/PN. Tpg. Based on the research used, the specifications of the research are descriptive. Juridical-normative, legislative, informal, and case approaches. Data collection techniques used are document studies and literature studies, with methods of data analysis normative-qualitative. Based on the results of the analysis of the settlement of non- performance in the online derivative agreement in the judgment No. 12/Pdt.G/2020/PN. Tpg, the judge's assembly rejected the petitioners' claims in its entirety because they did not meet the subjective conditions of the agreement, and the objective valid condition of an agreement is that there is no particular thing, and cause is not legal that is contrary to the law.